Evaluation of Antimicrobial Profile of Some Novel 1, 3, 4-Oxadiazole Derivatives Followed by Molecular Docking Against 3G7E Bacterial DNA Gyrase - Bhaumik, Asish; Chinna Eswaraiah, M.; Chakraborty, Raja (Journal of Drug Delivery and Therapeutics, 2019)
The main aim and objective of the present research work was the design, synthesis, spectral characterization and evaluation of in vitro antimicrobial profile of some novel oxadiazole derivatives followed by molecular docking studies against bacterial DNA gyrase. The molecular structures of the synthesized compounds were assigned by IR, NMR and Mass spectral analysis. Molecular docking studies were carried out by AUTO DOCK programme. The in vitro antibacterial and antifungal activities were done by paper disk diffusion and agar streak dilution technique. In silico molecular docking studies the binding energy  of synthesized compounds (AB1-AB8)  were found to be  -7.66, -7.67, -7.12, -7.12, -6.59, -6.46, -7.35, -5.09 which indicated that the compound had the high binding affinity towards the  bacterial DNA gyrase with PDB id 3G7E and inhibit the function  topoisomerase in comparison with standard drug ciprofloxacin (-7.44). The preliminary antimicrobial screening displayed that most of the synthesized compounds were executed moderate to good antimicrobial activity against  following bacteria: S. aureus (ATCC 9144), B. subtilis (ATCC 6633), S. epidermidis (ATCC 12228), P. Aeruginosa (ATCC27853), E.coli (ATCC25922), V. cholerrae (ATCC14035) and fungi:  A. Niger (ATCC 9029), A.flavus (ATCC204304), C. albicans (ATCC10231) and B. dermatitis (ATCC 26199) etc. All the synthesized compounds exhibited moderate to good antibacterial and antifungal activity with an MIC range of 12-37µg/ml.  Among these eight synthesized oxadiazole derivatives, compound AB1; AB2 and AB7 were found to be very good antibacterial as well as antifungal potentiality with an MIC range of 13-12 µg/ml; 7-10 µg/ml and 15-18 µg/ml.Keywords: Molecular docking; NMR; disk diffusion; antibacterial; antifungal and MIC etc.